تأثير العائل النباتي لمن الدراق الأخضر Myzus persicae (Homoptera: Aphididae) في بعض مؤشرات دورة حياة المفترسHippodamia variegata (Goeze) (Coleoptera:Coccinellidae) - أحمد, محمد; مفلح, ماجدة; مخلوف, هبة (Latakia University Journal -Biological Sciences Series, 2018)
A laboratory study was carried out on the predator Hippodamia variegata (Goeze) (Coleoptera: Coccinellidae) using the green peach aphid, Myzus persicae (Homoptera: Aphididae) as prey, in laboratory conditions after rearing it on five host plants which were (pepper, tobacco, tomato, eggplant and cucumber). The present study aimed to determine the impact of prey host plants on some developmental parameters of H. variegata. Results showed that the lowest developmental time from eggs hatching to emergence of adults was (10.43±0.63) days on pepper, while the longest developmental time was on eggplant (13.56±1.04) days. The lowest larval developmental duration was (6.37±0.53) days on pepper, and the longest duration was on eggplant (8.06±0.63) days. Also The shortest pupal duration was on pepper (2.35±0.45) days, and the longest period was on eggplant (4.25±0.43) days. The ratio of larval survival was affected by host plant, this ratio was maximum on pepper 82%, and was minimum on eggplant 40%. The results of statistical analysis showed that there were significant differences between the five host plants in all studied biological characteristics except third larval instar and pre-pupa stage. أجريت دراسة مخبرية على المفترسHippodamia variegata (Goeze) (Coleoptera: Coccinellidae)، استخدمَ فيها من الدراق الأخضر Myzus persicae (Homoptera : Aphididae) كفريسة ضمن الظروف المخبرية وذلك بعد تربيته على خمس عوائل نباتية (الفليفلة، التبغ، البندورة، الباذنجان والخيار). هدفت الدراسة إلى معرفة تأثير النبات العائل لمن الدراق الأخضر في بعض مؤشرات دورة حياة المفترس H. vareigata. أظهرت النتائج أن مدة التطور بدءاً من فقس البيض وحتى انبثاق الحشرة الكاملة بلغت بالمتوسط (10.43±0.63) يوماً على الفليفلة وهي أقل مدة تطور، بينما كانت أعلى مدة تطور على الباذنجان حيث بلغت (13.56±1.04) يوماً. كانت أقصر مدة استغرقها الطور اليرقي على الفليفلة حيث بلغت (6.37±0.53) يوماً بينما أعلى مدة تطور كانت على الباذنجان حيث استغرقت (8.06±0.63) يوماً. كما كانت أقصر مدة تعذر على الفليفلة حيث بلغت (2.35±0.45) يوماً وأطول مدة تعذر كانت على الباذنجان (4.25±0.43) يوماً. تم حساب نسبة بقاء اليرقات على قيد الحياة حيث كانت أعلى نسبة على الفليفلة 82% وأقل نسبة على الباذنجان 40%. بينت نتائج التحليل الإحصائي وجود فروقات معنوية بين العوائل النباتية الخمسة في جميع مؤشرات دورة الحياة المدروسة باستثناء العمر اليرقي الثالث وفترة ما قبل التعذر.